Achievement Motivation Among Members of a University Esports Organization - Aris Setiawan; Hardani Widhiastuti; Margaretha Maria Shinta Pratiwi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The rapid growth of esports in Indonesia has led many universities to establish esports organizations as platforms for fostering students' interests, talents, and achievements in competitive gaming. In this context, student members of esports organizations are required to balance academic responsibilities, organizational involvement, and competitive demands, making achievement motivation an important psychological factor in supporting their success. This study aimed to understand achievement motivation among university students who are members of an esports organization and to identify the factors influencing their motivation. This study employed a qualitative case study approach involving a university esports organization in Surakarta. Three student members were selected using purposive sampling. Data were collected through in-depth interviews and documentation and analyzed using Braun and Clarke's thematic analysis. The findings identified three main themes reflecting achievement motivation among students: achievement as a form of personal accomplishment and self-recognition, social support and a sense of belonging within the esports community, and leadership and responsibility as drivers of achievement motivation. Furthermore, achievement motivation was influenced by internal factors, including personal goals, aspirations for self-development, self-evaluation, and satisfaction with achievements, as well as external factors such as social support, organizational environment, and competitive experiences. The findings imply that university esports organizations should not only focus on competitive performance but also foster supportive social environments and leadership development to enhance students' achievement motivation and organizational engagement.Pertumbuhan esports yang semakin pesat di Indonesia telah mendorong berbagai perguruan tinggi membentuk organisasi esports sebagai wadah untuk mengembangkan minat, bakat, dan prestasi mahasiswa dalam bidang esports. Dalam aktivitasnya, mahasiswa anggota organisasi esports dihadapkan pada tuntutan akademik, organisasi, dan kompetitif yang memerlukan motivasi berprestasi sebagai faktor psikologis penting untuk menunjang keberhasilan mereka. Penelitian ini bertujuan untuk memahami motivasi berprestasi pada mahasiswa anggota organisasi esports di perguruan tinggi serta mengidentifikasi faktor-faktor yang memengaruhinya. Penelitian ini menggunakan pendekatan studi kasus kualitatif pada sebuah organisasi esports di salah satu perguruan tinggi di Surakarta. Partisipan penelitian terdiri atas tiga mahasiswa anggota organisasi esports yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui wawancara mendalam dan dokumentasi, kemudian dianalisis menggunakan analisis tematik Braun dan Clarke. Hasil penelitian mengidentifikasi tiga tema utama yang merefleksikan motivasi berprestasi mahasiswa, yaitu prestasi sebagai bentuk pencapaian dan pengakuan diri, dukungan sosial dan rasa memiliki dalam komunitas esports, serta kepemimpinan dan tanggung jawab sebagai pendorong motivasi berprestasi. Selain itu, motivasi berprestasi dipengaruhi oleh faktor internal yang meliputi target pribadi, keinginan untuk berkembang, evaluasi diri, dan kepuasan atas pencapaian, serta faktor eksternal berupa dukungan sosial, lingkungan organisasi, dan pengalaman kompetitif. Temuan penelitian mengindikasikan bahwa organisasi esports di perguruan tinggi perlu tidak hanya berfokus pada pencapaian kompetitif, tetapi juga membangun lingkungan sosial yang suportif serta mengembangkan kapasitas kepemimpinan mahasiswa untuk meningkatkan motivasi berprestasi dan keterlibatan organisasi.